Biaxial magnetic alignment in twinned REBa2Cu3Oy superconductors. (13th October 2016) - Horii, S; Nishioka, T; Arimoto, I; Fujioka, S; Doi, T
Abstract: Biaxial magnetic alignment of REBa2 Cu3 O y (RE123, RE = Y, Nd, Sm, Dy, and Er) superconductor powders containing twin microstructures was demonstrated. Appropriate choice of RE effectively improved the degrees of in-plane and c -axis orientation in RE123 powder samples aligned under modulated rotating magnetic fields at room temperature. From the relationship between the magnetic field strength and the degrees of orientation, it is concluded that heavy RE ions induced the improvement of the in-plane magnetic anisotropies in RE123 grains with twin microstructures.